Pengaruh kepuasan konsumen dan nilai utilitarian terhadap niat beli ulang melalui booking online (study kasus pada platform tiket.com) - Astuti, Ni Luh Gde Sari Dewi (Journal of Information System, Applied, Management, Accounting and Research; Vol 9 No 1 (2025): JISAMAR (December-February 2025), 2025)
The development of technology is increasingly rapid and continues to be felt by various sectors, such as tourism, particularly in the Hotel Industry. Reservations or room orders at a hotel come from guests directly or the hotel in collaboration with travel agents, companies, governments, or online travel agents (OTA). tiket.com is one of the start-up companies. This study focuses on booking hotel rooms via the tiket.com platform. 126 Respondents in this study were guests / consumers who had made hotel room reservations via tiket.com more than once or even many times. The positive impact of the consumer satisfaction variable on repurchase intentions was accepted. This shows that consumer satisfaction felt by tiket.com consumers has a positive impact on consumer repurchase intentions. The higher the level of consumer satisfaction, the higher the consumer's repurchase intention will be. The positive influence of the utilitarian value variable on repurchase intentions was accepted. This shows that the utilitarian value owned by tiket.com consumers has a positive impact on consumer repurchase intentions.